Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $k\ge 2 $ and $m_{1},\ldots,m_{k}$ in $\mathbb{N}$ with $\gcd(m_{i},m_{j})= 1 \ (i \ne j)$.

  1. We show that $f(x) = x,\ldots,x)$ ist a ring isomorphism $f: \mathbb{Z}/ m\mathbb{Z} \rightarrow \mathbb{Z} / m_{1} \mathbb{Z} \times\cdots\times \mathbb{Z}/ m_{k}\mathbb{Z}$

  2. We show that for $y_{1},\ldots,y_{k} \in \mathbb{Z}$ it follows that there exists a y in $\mathbb{Z}$ so that $y\equiv y_{1} \pmod {m_{1}}, y\equiv y_{k} \pmod {m_{k}} \Leftrightarrow m_{1}|y-y_{1},\ldots, m_{k}| y- y_k$

    1). We know that $\mathbb{Z}/ m\mathbb{Z}$ is a Ring, therefore with $f(xy)=(xy,\ldots,xy)=(x,\ldots,x)(y,\ldots,y) = f(x)f(y)$ and $f(x+y)=(x+y,\ldots,x+y) = (x,\ldots,x)+(y,\ldots,y) = f(x)+f(y)$ f is a homomorphism . Suppose $x = y \pmod m$ . then with $m_{i}|m$ and $m|x-y \Rightarrow m_{i}| x-y$, it follows that} $x=y \pmod m_{i}$ and thus $f$ is a well defined ring homomorphism.

If $x \bmod n \in \operatorname{ker}(f)$, then it follows that $m_{j}|x$ for $j=1,\ldots,k$ and because $m_{k}$ ist relatively pairwise coprime, then also $x \bmod m = 0$. Thus f is injective. Because of $|\mathbb{Z} / m \mathbb{Z} | = | \mathbb{Z} / m\mathbb{Z}_{1}\times\cdots\times \mathbb{Z}/m \mathbb{Z}_{k}|$, $f$ is also surjective. Thus $f$ is an isomorphism.

2). The existence of such an y is equivalent to the surjectivity of $f$ , and the uniqueness in $0\le x \le m_1,\ldots, m_k-1$ follows from the injectivity.



share|cite|improve this question
Can you choose the $m_i$ freely? In that case, just choose $y=y_1$ and $m_i=y_1-y_i$. – Jesko Hüttenhain Oct 27 '11 at 11:16
Excuse me, I added the premise now. – VVV Oct 27 '11 at 11:19
I think this has to do with the chinese remainder theorem if I am not mistaken. – user17090 Oct 27 '11 at 11:20
You want the Chinese Remainder Theorem. – Brian M. Scott Oct 27 '11 at 11:20
algebra is a deprecated tag. I removed it for a reason. Please don't add it again. – J. M. Oct 27 '11 at 12:07

Begin by looking up the Chinese Remainder Theorem in any intro Number Theory textbook, or on a web search engine.

share|cite|improve this answer
So I should prove the Chinese Remainder Theorem. Since this… was the foregoing question, I suppose I must use this somehow? – VVV Oct 27 '11 at 11:32
What I wrote was that you should look up the Chinese Remainder Theorem. Did you? – Gerry Myerson Oct 27 '11 at 11:46
I edited my question, is my proof correct? – VVV Oct 27 '11 at 12:01

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.